Pengaruh Keputusan Investasi, Keputusan Pendanaan, Kebijakan Dividen Dan Kinerja Keuangan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2020 - Heri Enjang Syahpura; Owen De Pinto Simanjuntak; Idahwati; Minarni Maduwu (Universitas Sari Mutiara Indonesia, 2023)
This study aims to determine the effect of investment decisions, funding decisions, dividend policies and financial performance on firm value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. This research is a quantitative research using secondary data. There are 51 populations in the study and a sample of 9 manufacturing companies in the food and beverage sub-sector using the documentation method. The sampling technique used was purposive sampling. The data analysis technique used descriptive statistical test, classical assumption test, multiple linear regression and hypothesis testing. The results of the study indicate that investment decisions have no effect on firm value. Funding decisions have no effect on Company Value. Dividend Policy has no effect on Firm Value and Financial Performance has no effect on Firm Value with Investment Decisions, Funding Decisions, Dividend Policy and Performance. Financial influences on firm value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange at a strong level and a determination value of 0.592. This shows that firm value is influenced by investment decisions, funding decisions, dividend policies and financial performance by 59.2%, while the remaining 40.8% is influenced by other factors not examined in this study.